Fabricación y análisis de propiedades físicas y mecánicas de un adoquín para jardineras reutilizando plásticos y envases tetrapack - Contreras Ponce, Edgar Manuel (2023)
The use of plastic and tetrapack, recycled in the manufacture of products for use in the construction of social housing, especially paving stones for residential use instead of the traditional ones, focused on the comparison of their physical and mechanical properties. In recent decades, plastic materials and the so-called tetrapak have been used for reuse in the development of products for the construction of homes, furniture, paving stones, among others. But the raw material used for the elaboration of these products has been mainly plastic, leaving the tetrapack material, mainly as raw material for its reuse in the manufacture of containers. However, there are already initiatives for the recycling of the tetrapack in the manufacture of aluminum products and materials for the construction of houses or furniture. In this regard, research work has been carried out for the manufacture and use of tetrapack and plastic in the manufacture of paving stones. The proposed project is carried out through experimental research, through which it will be possible to compare the physical and mechanical properties of a traditional paving stone and a paving stone with recycled material for planters, that is to say, we will have a quantitative approach allowing us to quantify the dosage of the aggregates and achieve a dosage that adapts to the standards for resistance and national paving stone manufacturing regulations.